How can Team performance in organizations be promoted? A shared leadership framework mediated by team psychological safety and moderated by team identification - Pires, Beatriz Rebordão (2020)
Shared leadership is a topic that has been growing in importance both for researchers and practitioners over the past few years. In fact, several studies have been conducted on the influence that shared leadership produces on team performance. However, there is still little research about the underlying factors that mediate and moderate the relationship between these two variables. Hence, the purpose of this study is to analyze the relationship between shared leadership and team performance through team psychological safety and for different levels of team identification. The study was conducted through self-reported questionnaires involving 86 people who comprised 27 teams. Data was collected in different countries and from several industries and the questionnaires were developed based on validated scales. The results, conducted in SPSS by using PROCESS macro, provided support for the direct relationship between shared leadership and team performance. Nevertheless, the results did not provide support for the mediating role of team psychological safety between shared leadership and team performance, for the moderation role of team identification and neither for the moderated mediation hypothesis. In future studies, researchers should not only consider other impactful factors that may affect the relationship between shared leadership and team performance, but also collect data from multiple moments in time. This paper sheds light on the importance that is for organizations nowadays to promote shared leadership environments where people are encouraged to see both themselves and their colleagues as potential leaders in order to succeed.